Utility of C-reactive protein and hematological parameters in the detection of neonatal sepsis - Mannan, MA; Shahidullah, M; Noor, MK; Islam, F; Alo, D; Begum, NA (Mymensingh Medical Journal, 2010)
Mymensingh Med J. 2010 Jul;19(2):259-63. The abstract of this article is available on the PubMed website